PERSONAL HYGIENE, SANITASI DAN ANGKA KUMAN ALAT MAKAN PADA SENTRA PEDAGANG MAKANAN JAJANAN DI KAMP. SOLOR KOTA KUPANG - , Enni Rosida Sinaga; , Dra. Susi Irayati, Apt, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Introduction: Food and drink are human beingâs daily need for living, growing and developing. To contribute well in humanâs body, food and drink should meet nutrition, health, nature, and hygiene indicators. Therefore, food and drink treating management are needed by considering environmental sanitation, personal, and eating utensils hygiene. Based on assumption, in Indonesia 80% of food and drink related sicknesses were spread from the food. Diarrhea out break is frequently happened to people in Kupang as it was recorded from December 2008 to January 3th 2009